Błędy atrybucyjne — ich psychologiczna dystrybucja, możliwości oceny i eliminacji w procesie translatorskim - Warchał, Mateusz (Przekłady Literatur Słowiańskich, 2013)
Attributive errors — their psychological distribution, possible evaluation and elimination in the translating process This paper attempts to provide for the psychological mechanisms of attribution, which appear in secondary text reception and evaluation of the role of the interpreter. The mechanisms described in the article relate to the difference in the perspective of the actor (the translator) and the observer (reader) and are described in the context of the stereotypes that appear in the source text and secondary text. The author acknowledges that the process of stereotyping is inevitable and at each step the reader asks the question about the (non) translatability is well founded, but is doomed to impose excessive “psychologization”. Key words: attribution, fundamental attribution error, stereotyping, the process of translation.